Pengembangan Usaha Olahan Tomat Kelompok Wanita Tani di Desa Darsono Kabupaten Jember - Kuswardhani, Nita; Andi Eko Wiyono; Nidya Shara Mahardika (Universitas Muhammadiyah Surakarta, 2025)
Darsono Village, Arjasa District, is one of the villages produce organic tomatoes in Jember Regency which are very abundant. The farmer faced the problem of low selling prices for tomatoes, especially during the harvest season. Therefore, PROBANGDEBI is carried out in collaboration with farmer woman’s group in local villages try to add the value of tomato. This activity aims to diversify processed tomatoes effectively and to form new business groups. This activity, which was carried out in Darsono Village, was attended by 15 women. The activities carried out are in the form of assistance and training in diversifying tomato processing to increase knowledge and skills. In this training, tomatoes are processed into tomato pureee, tomato jam, torakur, and chili sauce. Product processing is provided with material delivery to prioritize food safety and CPPOB. This is important to increase understanding so that the products made are safe for consumption. Material on food safety and CPPOB was provided by the speaker using presentation and discussion methods. The training carried out is not only on the processing process. The BMC material was provided by the speaker as additional understanding for the participating mothers so that the target market for the product could be targeted. At the end of the training activities, a group of women farmers called Putri Mandiri was formed in Darsono Village. The group that has been formed endeavors to remain active so that activities can be sustainable and can improve the economy of the Darsono Village community in general.